PEMETAAN HAFIDZ JUZ 30 BERPRESTASI MENGGUNAKAN METODE K-MEANS CLUSTERING (STUDI KASUS : Siswa-Siswa MI Al-As'ad) - Maulana Bintang , Rizki; Kadek Dwi Nuryana , I (Inovate, 2024)
MI Al-As'ad Brambang is an educational institution equivalent to elementary school that organizes the Tahfidz Juz 30 program to provide motivation and enthusiasm for learning to its students. Therefore, this research focuses on the development of an Outstanding Hafidz Juz 30 Mapping Information System using the K-Means Clustering method. The K-Means Clustering method is used in this study to select and group students based on several predetermined score criteria. The information system developed will assist teachers in maximizing learning outcomes and memorizing Juz 30 by providing learning assistance that suits the needs of each group of students. Thls research is expected to provide benefits both academically and practically. Academically, this information system can group students in several achievement categories, so that teachers can provide assistance according to the needs of each group. Practically, this information system can be applied throughout the MI Al-As'ad Brambang environment. Thls research is also expected to be a reference for further researchers in developing or improving the Juz 30 hafidz mapping system using the web-based K-Means Clustering method. Keywords : Mapping, Hafidz Juz 30, K-Means Clustering, Web